Discordant Diagnosis of Malaria in a Family of Child Refugees from Sierra Leone - Stephanie K Yanow; Daniel Gregson; Rupesh Chawla (Canadian Journal of Infectious Diseases and Medical Microbiology)
The clinical presentation and diagnosis of malaria involving a family with seven children who arrived in Canada as refugees is reported. Discrepancies in front-line testing using microscopy and rapid diagnostic tests compared with confirmatory testing using real-time polymerase chain reaction in this cluster of symptomatic and asymptomatic patients were identified.